A SURVEY OF URINARY BLADDER INJURIES IN ABBOTTABAD - Khan, Raza Muhammad; Nawaz, Muhammad; Raza, Nabeela; Sultan, Noreen (Journal of Ayub Medical College Abbottabad, 2004)
Background: Injury of urinary bladder is not very uncommon. It has iatrogenic and non iatrogenic causes. This study was designed to determine the pattern, mode of diagnosis and management of urinary bladder injuries presenting at Ayub Teaching Hospital, Abbottabad. Methods: Ten years hospital record of urinary bladder injuries reporting at Urology, Surgical and Gynaecology wards of Ayub Teaching Hospital, Abbottabad was analysed. The cause of injury, associated injuries, diagnostic method and management protocols were analyzed. Results: During 10 years period 260 patients were treated for bladder injuries. The age range was from 5-75 years while there were more males than females. In 35% the injuries were due to RTA, in 20% by a fall from a height, in 10% by a gun shot wound and in the remaining 35% the injury was iatrogenic. Gynaecological procedures were the major cause for iatrogenic bladder injuries. Conclusions: Most of the bladder injuries seen at our hospital are due to road traffic accidents or iatrogenic causes. Both of these factors can be minimized by taking appropriate steps to improve road safety and operative procedure safety respectively. Keywords: Urinary Bladder, Injury, etiology, management, diagnosis